Representasi Identitas Etnis Cina dalam Film Dimsum Martabak (2018) - Yolanda Audrey; Turnomo Rahardjo; Triyono Lukmantoro (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Anti-Chinese sentiments spread since the Dutch colonial era and the emergence of regulations that are burdensome for ethnic Chinese are the background for the persistence of stereotypes and acts of discrimination to this day. As a result, films that raise issues about ethnic Chinese present stereotypes that are deeply embedded in the cultural construction of society. This research aims to find out the representation of Chinese ethnic identity and intersectionality in the film Dimsum Martabak. This research uses Identity Negotiation Theory, constructivism paradigm, and data analysis techniques using John Fiske's semiotic analysis. The results of this study show that the Chinese ethnic identity depicted in the film normalizes and confirms the stereotypes believed by the wider community. In addition, the Chinese ethnic intersection shown in the movie is still difficult to find. The stereotypes displayed in the film are in the form of Chinese ethnic exclusivity and Chinese ethnic dominance in the economic and business fields. The exclusivity of ethnic Chinese in the film is shown through cultural elements that are still oriented and adapted from Chinese culture, difficult to mingle and be open to different cultures, and drop others who are culturally different. Chinese domination in the economic and business fields is shown through the portrayal of Chinese ethnic characters as entrepreneurs who come from wealthy families. Based on the results of this study, recommendations for future research are to examine the forms of stereotypes in various media using more varied cultural communication theories, as well as adding references to Chinese ethnic identity and stereotypes in it for depth and novelty of research.